The Effect Of Fe Tablet Consumption On The Incidence Of Anemia In Female Adolescents At Sma Negeri 1 Praya In Mid-Year 2024: Study Cohort - Muqarrobin, Aoladul; Wiksuarini, Erwin; Halimatunnisa, Maulin; Rukmana, Baiq Fitrihan; Amrullah, Muhammad; Amanupunnyo, Notesya A. (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2025)
Anemia is a condition where the hemoglobin level is less than expected according to age and gender. Data from the Ministry of Health in 2013 showed that the prevalence of nutritional anemia in the adolescent age group (≥15 years) was 22.2%. The impact of anemia can cause decreased learning achievement in adolescent girls. The purpose of the study was to determine the effect of Fe Tablet Consumption on the incidence of anemia in adolescent girls at SMA Negeri 1 Praya Tengah in 2024. The analytical survey research method with a cohort study approach, the population of adolescent girls were students of SMA Negeri 1 Paraya Tengah, a sample of 96 people was divided into two groups, namely the exposed group 48 and the unexposed group 48 people. The results of the study showed that in the exposed group given Fe, the number of anemia cases was 8 (16.7%) and those who were not anemic were 40 (83.3%), while in the unexposed group the number of anemia was 32 (66.7%) and those who were not anemic were 16 (33.3%). The results of the Che-square statistical test showed P <0.001, meaning that there was a relationship between consumption and the incidence of anemia in adolescent girls, students of SMA Negeri 1 Praya Tengah. There needs to be information and education activities to increase adolescent knowledge about anemia, in this case the school can collaborate with the nearest Community Health Center to carry out health promotion efforts, especially regarding anemia and efforts to provide healthy canteens at schools that sell nutritious food to prevent students from buying unhealthy snacks.